Low-extraction bidentate modified resin for fuel cell ethylene glycol coolant, preparation method and deionizer
Patent Information
- Application Number
- CN202611183484.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-23
AI Technical Summary
该体系能够在短时间内降低冷却液电导率,但其缺点在于:第一,普通混床树脂对腐蚀金属离子缺乏选择性,所有阳离子和阴离子均共同消耗树脂容量;第二,在高温乙二醇/水体系中,强碱阴离子交换树脂可能出现热稳定性不足、功能基团降解或有机胺析出等问题;第三,冷却液中的Fe、Al、Cu、Zn等金属离子可能催化乙二醇氧化降解,进一步加快冷却液电导率上升;第四,普通树脂自身可能含有Na+、K+、Ca2+、Mg2+、Cl-、有机低分子或金属背景离子,若未经充分低析出处理,反而可能对低电导冷却液造成污染
本发明通过在国产大孔树脂基体上引入亚氨基二乙酸基团和膦酸基团,形成双配位金属离子捕获体系,使树脂同时具备对二价过渡金属离子和高价金属离子的捕获能力。
Smart Images

Figure CN122958630A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ethylene glycol coolant technology for fuel cells, and more specifically, to a low-precipitation dual-coordination modified resin for ethylene glycol coolant in fuel cells, its preparation method, and a deionizer. Background Technology
[0002] Hydrogen fuel cell systems generate a significant amount of heat during operation, requiring a liquid cooling system to maintain the stack and auxiliary components within a reasonable temperature range. For fuel cell heavy-duty trucks, logistics vehicles, buses, engineering vehicles, and stationary fuel cell systems, the liquid cooling system typically uses pure water, ethylene glycol / water mixed coolants, or fuel cell-specific low-conductivity coolants as the heat transfer medium. Due to the high voltage, strong insulation, and long-term stable operation requirements of fuel cell stacks, the coolant must maintain a low conductivity over a long period to reduce the risk of leakage current and ensure the safe and stable operation of the system.
[0003] During the long-term circulation of a fuel cell liquid cooling system, cooling pipes, joints, heat exchangers, water pumps, metal components, and stack materials may release metal ions such as Fe, Al, Cu, Zn, Ni, and Cr. Simultaneously, impurities such as carbon powder, graphite particles, and metal oxide particles may enter the coolant circulation system during stack operation. Ethylene glycol may also undergo oxidative degradation under conditions of high temperature, oxygen, water, and the presence of metal ions, producing conductive substances such as organic acid salts. These metal ions, inorganic anions, organic acid salts, and particulate contaminants can increase the coolant conductivity, accelerate the deionizer resin capacity consumption, shorten filter maintenance cycles, and potentially affect the insulation safety and long-term stability of the fuel cell system.
[0004] Existing fuel cell deionizers typically employ a mixed-bed system composed of strong acid cation exchange resins and strong base anion exchange resins. This system can rapidly reduce coolant conductivity, but it has several drawbacks: First, ordinary mixed-bed resins lack selectivity for corrosive metal ions, with all cations and anions contributing to resin capacity. Second, in high-temperature ethylene glycol / water systems, strong base anion exchange resins may experience insufficient thermal stability, functional group degradation, or organic amine precipitation. Third, metal ions such as Fe, Al, Cu, and Zn in the coolant may catalyze the oxidative degradation of ethylene glycol, further accelerating the increase in coolant conductivity. Fourth, ordinary resins may contain sodium (Na+). + K + Ca 2+ Mg 2+ Cl - Organic low-molecular-weight or metal background ions, if not adequately treated for low-deposition, may contaminate the low-conductivity coolant.
[0005] To reduce costs and improve system lifespan, existing technologies have proposed adding chelating resins or particulate filters to the front end of mixed-bed resins. However, directly purchasing commercial chelating resins and combining them with mixed-bed resins still presents the following problems: First, commercial chelating resins are mostly designed for water treatment, hydrometallurgy, or heavy metal wastewater applications, and may not be suitable for low-conductivity glycol coolants in fuel cells; second, commercial chelating resins may have issues such as high initial conductivity, soluble ion precipitation, TOC precipitation, and particle size mismatch with existing filter elements; third, single iminodiacetic acid-type chelating resins may have problems with Cu 2+ Zn 2+ Divalent transition metal ions have good capture ability, but Fe... 3+ Al 3+ There is still room for improvement in the compatibility with high-valence hard acid metal ions; fourth, if the chelating resin and the mixed bed resin are mixed disorderly, the high-purity mixed bed resin may still come into contact with the original contaminated coolant first, and cannot fully play its front-end protection role.
[0006] Therefore, there is a need to develop a low-precipitation modified resin material suitable for ethylene glycol coolants in fuel cells. This material should be based on a low-cost, domestically produced resin matrix, and through independent post-functionalization modification, introduce multiple metal ion coordination sites. After undergoing low-precipitation pretreatment, it should be suitable for low-conductivity, high-temperature ethylene glycol coolant systems. Simultaneously, this material needs to be positioned along the coolant flow direction at the deionizer inlet side to preferentially capture corrosive metal ions, thereby reducing the load on the downstream high-purity mixed-bed resin and extending the overall lifespan of the deionizer. Summary of the Invention
[0007] In view of this, the present invention aims to at least partially solve one of the technical problems in the aforementioned related technologies. To this end, the present invention introduces iminodiacetic acid groups and phosphonic acid groups onto a domestically produced macroporous resin matrix to form a dual-coordinate metal ion capture system, enabling the resin to simultaneously capture divalent transition metal ions and high-valent metal ions. This modified resin is placed on the inlet side of the deionizer, which can preferentially capture corrosive metal ions in the coolant, reduce the impact of metal ions on the downstream mixed bed resin, and thus extend the low conductivity maintenance life of the high-purity mixed bed resin.
[0008] The first aspect of this invention provides a low-precipitation dual-coordination modified resin for use in ethylene glycol coolants for fuel cells, the low-precipitation dual-coordination modified resin comprising: Macroporous organic resin matrix; iminodiacetic acid groups and phosphonic acid groups grafted onto the macroporous organic resin matrix.
[0009] In a preferred embodiment, the macroporous organic resin matrix includes at least one of macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy-based macroporous resin, amino-based macroporous resin, and weakly basic macroporous resin that can be modified secondary.
[0010] In a preferred embodiment, the iminodiacetic acid group is used to capture Cu. 2+ Zn 2+ Ni 2+ Fe 2+ At least one of them.
[0011] In a preferred embodiment, the phosphonic acid group is used to capture Fe. 3+ Al 3+ Cr 3+ At least one of them.
[0012] In a preferred embodiment, the content of the low-iminodiacetic acid group is 0.2~2.5 mmol / g; the content of the phosphonic acid group is 0.05~1.5 mmol / g; and the total metal coordination capacity is 0.5~3.5 mmol / g.
[0013] In a preferred embodiment, the low-precipitation dual-coordination modified resin has a particle size of 0.30~1.25 mm, a water content of 35~75%, a wet apparent density of 0.60~0.90 g / mL, a pore size of 10~100 nm, and a specific surface area of 20~800 m². 2 / g.
[0014] In a preferred embodiment, after the low-precipitation dual-coordination modified resin is pre-stabilized in a 50% ethylene glycol-water mixture at 90-105°C for 24-120 hours, the conductivity of its effluent is ≤20μS / cm, preferably ≤10μS / cm; and the TOC is ≤30mg / L, preferably ≤15mg / L.
[0015] A second aspect of the present invention provides a method for preparing the low-precipitation dual-coordination modified resin, comprising the following steps: S1. Pre-treat the macroporous organic resin matrix to obtain the pre-treated macroporous organic resin, and remove inorganic salts, low molecular weight organic matter and mechanical impurities from the resin. S2. The pretreated macroporous organic resin matrix is swollen to obtain swollen resin. S3. React the swollen resin with iminodiacetic acid salt to introduce iminodiacetic acid groups and obtain the first modified resin; S4. Further amination of the remaining reactive sites of the first modified resin, and introduction of phosphonic acid groups through phosphonomethylation reaction to obtain a dual-coordination modified resin. S5. The dual-coordination modified resin is end-capped to seal residual chloromethyl sites, epoxy sites, or free reaction sites. S6. The end-capped dual-coordination modified resin is subjected to acid washing, ultrapure water washing, ethylene glycol-water replacement and pre-stabilization treatment in sequence to obtain the low-precipitation dual-coordination modified resin.
[0016] In a preferred embodiment, the pretreatment includes washing the macroporous organic resin matrix sequentially with ethanol, deionized water, 0.1~2.0 mol / L hydrochloric acid solution, deionized water, 0.1~2.0 mol / L sodium hydroxide solution, and deionized water until the conductivity of the washing solution stabilizes.
[0017] In a preferred embodiment, in step S2, the swelling treatment is performed by impregnation with N,N-dimethylformamide, dimethyl sulfoxide, ethanol, water, methanol, and isopropanol.
[0018] In a preferred embodiment, the swelling temperature is 20~80℃ and the swelling time is 2~24h.
[0019] In a preferred embodiment, in step S3, the iminodiacetic salt includes at least one of disodium iminodiacetic salt, trisodium iminodiacetic salt, and salts formed by in-situ neutralization of iminodiacetic salt with one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide.
[0020] In a preferred embodiment, the reaction temperature in step S3 is 50~95℃, the reaction time is 4~36h, and the pH of the reaction system is 8~12.
[0021] In a preferred embodiment, the amination is performed using at least one of ammonia, ethylenediamine, diethylenetriamine, triethylenetetramine, ethanolamine, or diethanolamine.
[0022] In a preferred embodiment, the phosphine methylation reaction uses at least one of phosphorous acid, phosphonic acid, hypophosphoric acid, aminotrimethylenephosphonic acid, formaldehyde, or paraformaldehyde as a reaction raw material, the reaction temperature is 70~110 ℃, and the reaction time is 4~24 h.
[0023] In a preferred embodiment, in step S5, the end-capping treatment is performed using ethanolamine, glycine, diethanolamine, triethanolamine, sodium carbonate, sodium sulfite, sodium thiosulfate, or a combination thereof, with an end-capping temperature of 30~90℃ and an end-capping time of 2~24h.
[0024] In a preferred embodiment, step S6, the ethylene glycol-water replacement includes sequentially replacing the solution with a 20-30% ethylene glycol-water mixture, a 40-60% ethylene glycol / water mixture, and a fuel cell-specific ethylene glycol coolant; the pre-stabilization treatment temperature is 90-105°C, and the treatment time is 24-120 hours.
[0025] A third aspect of the present invention provides a deionizer for ethylene glycol coolant in a fuel cell. The deionizer includes a housing, a coolant inlet, a coolant outlet, and an inlet filter / flow distribution layer, a low-precipitation dual-coordination modified resin zone, a microporous partition, a high-purity mixed bed resin zone, and an outlet high-temperature fine filter layer, which are sequentially arranged inside the housing along the coolant flow direction.
[0026] In a preferred embodiment, the low-emission dual-coordination modified resin zone occupies 5-30% of the effective filling volume inside the deionizer, preferably 10-20%; the high-purity mixed-bed resin zone occupies 60-90% of the effective filling volume inside the deionizer, preferably 75-85%. It should be understood that low precipitation means that after the modified resin has undergone acid washing, ultrapure water washing, ethylene glycol-water replacement and high-temperature pre-stabilization, the conductive ions, organic matter and background metal ions released in the ethylene glycol-water system are within the acceptable range of the fuel cell coolant.
[0027] High-purity mixed bed resins include mixed bed resins formed by strong acid cation exchange resins and strong base anion exchange resins, as well as mixed bed resins for fuel cell coolants that have undergone low precipitation treatment, electronic grade mixed bed resins, or polishing grade mixed bed resins.
[0028] The microporous partition includes a PPS microporous partition, a PTFE support mesh, a PPS support mesh, a PEEK microporous partition, a PVDF microporous partition, or a combination thereof, preferably a PPS microporous partition; The microporous partition has a pore size of 50~500μm, preferably 150~300μm; and an open porosity of 30~70%, preferably 40~55%. The inlet filtration / flow layer includes a high-temperature filter screen, high-temperature filter cotton, PPS fiber felt, PTFE support mesh, porous partitions, or a combination thereof; The outlet high-temperature fine filtration layer is a PPS sintered filter, PPS fiber felt, PTFE filter, PES filter, glass fiber filter, or a combination thereof.
[0029] The deionizer is suitable for pure water, ethylene glycol coolant, ethylene glycol-water mixed coolant, or 50% ethylene glycol fuel cell-specific coolant; the operating temperature is -30~105℃, preferably -30~95℃ for long-term operation and enhanced verification at 100℃.
[0030] In a preferred embodiment, the deionizer has an initial pressure drop of ≤15kPa, preferably ≤12kPa, at a coolant flow rate of 10LPM; the outlet coolant conductivity is ≤5μS / cm, and the initial outlet conductivity is ≤1μS / cm.
[0031] A fourth aspect of this invention provides a hydrogen fuel cell liquid cooling system, comprising a hydrogen fuel cell heavy-duty truck, a hydrogen fuel cell logistics vehicle, a hydrogen fuel cell bus, a stationary fuel cell system, a fuel cell backup power system, or other electrochemical systems using a low-conductivity ethylene glycol / water coolant. The modified resin described above captures one or more corrosive metal ions (Fe, Al, Cu, Zn, Ni, Cr) in the ethylene glycol coolant of the fuel cell at the front end, and achieves low-conductivity polishing of the coolant through a high-purity mixed-bed resin at the back end.
[0032] It should be understood that the aforementioned ethylene glycol coolant includes pure ethylene glycol coolant, ethylene glycol-water mixed coolant, 50% ethylene glycol-water coolant, and low-conductivity ethylene glycol coolant specifically for fuel cells.
[0033] Compared with the prior art, the present invention achieves at least the following beneficial effects: This invention introduces iminodiacetic acid groups and phosphonic acid groups onto a domestically produced macroporous resin matrix to form a dual-coordinate metal ion capture system, enabling the resin to simultaneously capture divalent transition metal ions and high-valent metal ions.
[0034] The modified resin described in this invention is placed on the inlet side of the deionizer, which can preferentially capture corrosive metal ions in the coolant, reduce the impact of metal ions on the downstream mixed bed resin, and thus extend the low conductivity maintenance life of the high-purity mixed bed resin.
[0035] This invention employs acid washing, ultrapure water washing, end-capping, ethylene glycol-water replacement, and high-temperature pre-stabilization treatment to allow the modified resin to release soluble ions and low-molecular-weight substances in advance before entering the fuel cell coolant system, thereby reducing the risk of increased coolant conductivity due to resin precipitation.
[0036] This invention allows for internal upgrades using existing fuel cell deionizer housings, eliminating the need to redevelop the outer casing, interfaces, and vehicle mounting methods, thus reducing product development cycles and engineering implementation costs.
[0037] The microporous separator described in this invention is preferably a PPS microporous separator, which serves to partition, distribute, and prevent resin cross-contamination, rather than a high-resistance membrane filter, thus helping to maintain a low pressure drop at a coolant flow rate of 10 LPM.
[0038] This invention is applicable to high-temperature ethylene glycol coolant scenarios in heavy-duty truck fuel cells and can be used in hydrogen fuel cell heavy-duty trucks, logistics vehicles, buses, stationary fuel cell systems, and other low-conductivity coolant circulation systems. Attached Figure Description
[0039] Appendix Figure 1 This is a process flow diagram for preparing the low-precipitation dual-coordination modified resin of the present invention.
[0040] Appendix Figure 2 This is a schematic diagram of the IDA-phosphonic acid dual-coordination structure in the low-precipitation dual-coordination modified resin of the present invention.
[0041] Appendix Figure 3 This is a schematic diagram of the internal structure of the deionizer of the present invention.
[0042] Appendix Figure 4 This is a schematic diagram of the coolant flow direction and the metal ion front-end capture mechanism in the deionizer of the present invention.
[0043] Appendix Figure 5 This is a comparison chart of metal ion penetration curves for different resin systems in embodiments of the present invention.
[0044] Appendix Figure 3 In the diagram, 1 is the coolant inlet; 2 is the inlet filter / flow distribution layer; 3 is the low-precipitation dual-coordination modified resin zone; 4 is the PPS microporous baffle; 5 is the high-purity mixed bed resin zone; 6 is the outlet high-temperature fine filter layer; and 7 is the coolant outlet. Detailed Implementation
[0045] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0046] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0047] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0048] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0049] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0050] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0051] The sources of some components in the embodiments are as follows. These sources are merely examples and do not constitute a limitation on the scope of protection of this invention. In actual production, domestically sourced products with equivalent purity and technical specifications can be used as substitutes: Chloromethylated polystyrene-divinylbenzene macroporous resin, with a particle size of 0.315~1.25mm, chlorine content of 2.5~5.5mmol / g, and crosslinking degree of 6~12%, was purchased from Xi'an Lanxiao Technology New Materials Co., Ltd.
[0052] Macroporous styrene-divinylbenzene resin, epoxy-based macroporous resin, and weakly basic macroporous resin were purchased from Xi'an Lanxiao Technology New Materials Co., Ltd.
[0053] High-purity mixed-bed resin was purchased from Xi'an Lanxiao Technology New Materials Co., Ltd.
[0054] Iminodiacetic acid, CAS No. 142-73-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0055] Phosphorous acid, CAS No. 13598-36-2, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0056] Formaldehyde solution and paraformaldehyde were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0057] Ethylenediamine, diethylenetriamine, ethanolamine, diethanolamine, glycine, sodium carbonate, sodium hydroxide, hydrochloric acid, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and ethylene glycol were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0058] PPS microporous partitions, PPS support mesh, PTFE support mesh, PPS sintered filter sheets, and PPS fiber felt are made of materials that are resistant to ethylene glycol, resistant to 95~100℃, have low precipitation, and are compatible with the PPS+GF shell.
[0059] All other materials whose source is not disclosed are commercially available products.
[0060] Example 1
[0061] This embodiment provides a method for preparing a low-precipitation IDA-phosphonic acid dual-coordination modified resin, the process of which is as follows: Figure 1 This includes the following steps: S1. Resin matrix pretreatment: Weigh 1000g of chloromethylated polystyrene-divinylbenzene macroporous resin with a particle size of 0.50~1.00 mm, a chlorine content of 4.2 mmol / g, and a crosslinking degree of 8%; add it to 5L of ethanol and stir and wash for 2h, then filter; wash three times with deionized water; then add 5L of 1.0 mol / L hydrochloric acid solution and stir at 25℃ for 4h, then filter; wash with deionized water until the pH of the effluent is 5.5; then add 5L of 0.5 mol / L sodium hydroxide solution and stir for 2h, then wash again with deionized water until neutral to obtain the pretreated resin.
[0062] S2. Resin swelling: The pretreated resin is added to 4L of N,N-dimethylformamide / water mixed solvent, with a volume ratio of N,N-dimethylformamide to water of 7:3. The resin is swollen at 50℃ for 8 hours to obtain swollen resin.
[0063] S3. Grafting of iminodiacetic acid groups: Weigh 450g of iminodiacetic acid and add it to 2L of deionized water. Slowly add sodium carbonate to adjust the pH to 10, forming a sodium iminodiacetic acid solution. Add this solution to the swollen resin, then add 1L of N,N-dimethylformamide. React at 75℃ for 16h to allow some chloromethyl sites to undergo nucleophilic substitution with the iminodiacetic acid salt. After the reaction is complete, filter and wash successively with N,N-dimethylformamide, ethanol, and deionized water to obtain the first modified resin.
[0064] S4. Amination of Remaining Sites: The first modified resin was added to 3 L of a mixed solution of ethylenediamine and ethanol (volume ratio of ethylenediamine to ethanol: 1:3), and reacted at 60 °C for 8 h to convert the remaining chloromethyl sites into amino sites. After the reaction was complete, the resin was washed with ethanol and deionized water to obtain the amination resin.
[0065] S5. Phosphine Methylation: The amination resin was added to a reaction vessel along with 300g of phosphorous acid, 250g of 37wt% formaldehyde solution, and 3L of deionized water. The pH was adjusted to 1.5 with hydrochloric acid, and the reaction was carried out at 90℃ for 10 hours to induce phosphine methylation at the amino sites, introducing phosphonic acid groups. After the reaction, the resin was filtered and washed with deionized water until the pH of the washing solution reached 4, yielding crude IDA-phosphonic acid dual-coordination modified resin. A schematic diagram of the dual-coordination structure is shown below. Figure 2 .
[0066] S6. Residual Site Capping: The crude IDA-phosphonic acid dual-coordination modified resin was added to 3 L of 5 wt% ethanolamine aqueous solution and reacted at 60 °C for 6 h to cap residual chloromethyl sites and some active sites. After filtration, it was washed with deionized water.
[0067] S7. Acid washing and ultrapure water washing: Add the end-capped resin to 5L of 1.0mol / L hydrochloric acid solution and stir at 25℃ for 4h to convert the resin to the H-type state with low sodium and low metal background; after filtration, wash with ultrapure water until the conductivity of the effluent is lower than 20μS / cm.
[0068] S8. Ethylene glycol / water replacement and high-temperature pre-stabilization: The resin was successively replaced with 25% ethylene glycol-water solution and then with 50% ethylene glycol-water solution, with each replacement volume being 5 times the wet volume of the resin. The resin was then placed in 50% ethylene glycol-water solution and pre-stabilized at 95℃ for 48 hours. After pre-stabilization, the resin was washed with 50% ethylene glycol-water solution until the conductivity of the effluent stabilized, yielding a low-precipitation IDA-phosphonic acid dual-coordination modified resin.
[0069] In this embodiment, the modified resin contained 1.10 mmol / g iminodiacetic acid groups and 0.38 mmol / g phosphonic acid groups. After soaking in a 50% ethylene glycol / water solution at 95°C for 24 h, the effluent had a conductivity of 8.6 μS / cm and a TOC of 12.5 mg / L. (The last sentence appears to be incomplete and possibly refers to a different topic: "For Fe...") 3+ Al 3+ Cu 2+ and Zn 2+ The overall dynamic capture capability is significantly higher than that of unmodified resin.
[0070] Example 2
[0071] This embodiment provides a low-cost method for preparing IDA-phosphonic acid dual-coordination modified resin. The difference from Example 1 is that the amount of iminodiacetic acid used is 550g, the amount of phosphorous acid used is 180g, and the amount of 37wt% formaldehyde solution used is 160g, resulting in a higher proportion of iminodiacetic acid groups in the resin compared to the proportion of phosphonic acid groups. The remaining steps are the same as in Example 1.
[0072] The obtained modified resin contained 1.35 mmol / g iminodiacetic acid groups and 0.22 mmol / g phosphonic acid groups. This resin is effective against Cu... 2+ Zn 2+ and Ni 2+ It has a high capture capacity and is suitable for coolant systems with significant contamination from divalent transition metal ions such as copper and zinc.
[0073] Example 3
[0074] This embodiment provides an IDA-phosphonic acid dual-coordination modified resin with enhanced ability to capture high-valence metal ions. The difference from Example 1 is that the amount of iminodiacetic acid used is 350 g, the amount of phosphorous acid used is 420 g, the amount of 37 wt% formaldehyde solution used is 330 g, the phosphine methylation reaction time is 14 h, and the remaining steps are the same as in Example 1.
[0075] The obtained modified resin contained 0.86 mmol / g iminodiacetic acid groups and 0.62 mmol / g phosphonic acid groups. This resin is effective against Fe... 3+ And Al 3+ Its capture capability is enhanced compared to Example 2, making it suitable for aluminum alloy heat exchangers, metal joints, or Fe... 3+ Al 3+ Cooling systems for fuel cell heavy-duty trucks, which are prone to significant pollution.
[0076] Example 4
[0077] This embodiment provides a low-precipitation dual-coordination modified resin using an epoxy macroporous resin as a matrix. 1000g of domestically produced epoxy macroporous resin was weighed and washed sequentially with ethanol, deionized water, hydrochloric acid, and deionized water. Then, it was added to an aqueous solution of sodium iminodiacetic acid and reacted at 80°C for 12 hours to open the epoxy ring and introduce iminodiacetic acid sites. Subsequently, ethylenediamine was added for amination, and then phosphonic acid groups were introduced following the phosphonomethylation steps in Example 1. Finally, end-capping, acid washing, ultrapure water washing, ethylene glycol-water displacement, and high-temperature pre-stabilization treatment at 95°C for 10 hours were performed to obtain a low-precipitation dual-coordination modified resin using the epoxy macroporous resin route.
[0078] Compared with the chloromethylated resin route, the reaction conditions in this embodiment are milder and the initial chloride ion background of the resin is lower, making it suitable for applications with higher requirements for chloride ion precipitation control.
[0079] Example 5 (prepared using the modified resin of Example 1) This embodiment provides a deionizer for ethylene glycol coolant in fuel cells containing a low-emission IDA-phosphonic acid dual-coordination modified resin, see [link to documentation]. Figure 3The deionizer comprises a PPS+GF shell, a coolant inlet 1, a coolant outlet 7, and an internal filling structure. The effective internal filling volume of the deionizer is 1.2L. Along the coolant flow direction, the following layers are sequentially arranged: an inlet filter / flow distribution layer 2, a low-emission IDA-phosphonic acid dual-coordination modified resin zone 3, a PPS microporous baffle 4, a high-purity mixed-bed resin zone 5, and an outlet high-temperature fine filter layer 6. The inlet filter / flow distribution layer uses a combination of a PPS support mesh and a PPS fiber filter layer, with a thickness of 10mm, to intercept large particulate impurities and uniformly distribute the coolant flow field. The low-emission IDA-phosphonic acid dual-coordination modified resin zone is filled with IDA-phosphonic acid dual-coordination modified resin that has undergone acid washing, ultrapure water washing, ethylene glycol replacement, and 95℃ high-temperature pre-stabilization treatment. The filling volume is 0.18L, accounting for 15% of the effective internal filling volume. The PPS microporous separator is 2 mm thick with a pore size of 200 μm and an open porosity of 48%. It is used to separate the front-end dual-coordination modified resin zone from the rear-end high-purity mixed-bed resin zone. The high-purity mixed-bed resin zone is filled with domestically produced high-purity strong acid cation / strong base anion mixed-bed resin, with a filling volume of 0.96 L, accounting for 80% of the internal effective filling volume. The outlet high-temperature fine filtration layer uses PPS sintered filter sheets with a pore size of 60 μm to intercept fine resin particles and debris. A schematic diagram of the coolant flow direction and the metal ion front-end capture mechanism in the ionizer is shown below. Figure 4 The simulated contaminated coolant was prepared by mixing ethylene glycol and ultrapure water at a mass ratio of 50:50, with an initial conductivity of 100±5 μS / cm, a pH of 6.5–7.5, and Fe... 3+ The initial concentration was 1.0 mg / L, Al 3+ The initial concentration was 1.0 mg / L, Cu 2+ The initial concentration was 0.8 mg / L, Zn 2+ The initial concentration was 0.8 mg / L, Na + The initial concentration was 2.0 mg / L, Cl - The initial concentration was 3.0 mg / L, SO4 2- The initial concentration was 3.0 mg / L. The test temperature was 95℃, and the circulation flow rate was 10 LPM.
[0080] Under the above conditions, Fe in this embodiment 3+ Al 3+ Cu 2+ Zn 2+The times to reach C / C0=0.10 were 269h, 282h, 614h, and 633h, respectively; the times to reach C / C0=0.50 were 335h, 350h, 735h, and 760h, respectively; and the times to reach C / C0=0.95 were 423h, 441h, 897h, and 931h, respectively. Initially, the outlet conductivity was below 1μS / cm, and during operation, it remained below 5μS / cm. These results indicate that the low-precipitation IDA-phosphonic acid dual-coordination modified resin of this invention can preferentially capture corrosive metal ions before the coolant enters the downstream high-purity mixed-bed resin, thereby significantly delaying the penetration time of metal ions such as Fe, Al, Cu, and Zn.
[0081] Example 6
[0082] This embodiment provides a deionizer using the low-cost IDA-phosphonic acid dual-coordination modified resin prepared in Example 2 as the front-end protective layer. Its structure is the same as that in Example 5, except that the modified resin zone occupies 10% of the internal effective filling volume, and the high-purity mixed bed resin zone occupies 85% of the internal effective filling volume.
[0083] This embodiment is applicable to applications with high initial cost control requirements and high Cu content in the coolant. 2+ and Zn 2+ Fuel cell systems primarily polluted by divalent transition metal ions.
[0084] Example 7
[0085] This embodiment provides a deionizer using the high-valence metal-reinforced IDA-phosphonic acid dual-coordination modified resin prepared in Example 3 as the front-end protective layer. Its structure is the same as in Example 5, except that the modified resin zone occupies 20% of the effective internal filling volume, and the high-purity mixed-bed resin zone occupies 75% of the effective internal filling volume. This embodiment is suitable for heat exchangers containing aluminum alloys, those with many metal joints, or those containing Fe. 3+ Al 3+ Cooling systems for fuel cell heavy-duty trucks, which are prone to significant pollution.
[0086] Comparative Example 1 The same deionizer housing as in Example 5 was used, except that the internal region for the low-emission IDA-phosphonic acid dual-coordination modified resin was not included. Instead, the deionizer interior was primarily filled with a high-purity strong acid cation / strong base anion mixed bed resin. Dynamic circulation evaluation was conducted using the same simulated contaminated coolant and test conditions as in Example 5.
[0087] Under the above conditions, Fe in this comparative example 3+ Al 3+ Cu 2+ Zn 2+The times to reach C / C0=0.10 were 59h, 65h, 132h, and 143h, respectively; the times to reach C / C0=0.50 were 90h, 98h, 205h, and 220h, respectively; and the times to reach C / C0=0.95 were 131h, 142h, 302h, and 323h, respectively. These results indicate that while the existing mixed-bed resin system can reduce the coolant conductivity in the initial stage, the lack of a front-end metal ion selective capture layer means that the rear-end mixed-bed resin directly withstands the impact of metal ions such as Fe, Al, Cu, and Zn, resulting in a short metal ion penetration time.
[0088] Comparative Example 2 The deionizer housing and internal structure are the same as in Example 5, except that the metal ion capture layer on the inlet side uses a commercial iminodiacetic acid-type chelating resin, and the phosphonic acid group introduction and low-precipitation high-temperature pre-stabilization treatment described in this invention are not performed. The packing volume of the commercial IDA chelating resin is 0.18 L, and the packing volume of the high-purity mixed bed resin is 0.96 L.
[0089] Under the same test conditions as in Example 5, Fe in this comparative example 3+ Al 3+ Cu 2+ Zn 2+ The times to reach C / CO=0.10 were 101h, 112h, 238h, and 256h, respectively; the times to reach C / CO=0.50 were 145h, 158h, 330h, and 350h, respectively; and the times to reach C / CO=0.95 were 204h, 220h, 454h, and 477h, respectively. These results indicate that commercial IDA chelating resin effectively chelates Cu... 2+ Zn 2+ Divalent transition metal ions have a certain ability to capture them, but not Fe. 3+ Al 3+ The penetration delay effect of high-valence metal ions is limited, and the overall metal ion penetration time is shorter than that of the IDA-phosphonic acid dual-coordination modified resin system of the present invention.
[0090] Comparative Example 3 Using domestically produced macroporous chloromethylated styrene-divinylbenzene resin as the matrix, iminodiacetic acid groups were introduced only through a post-functionalization reaction, without amination or phosphomethylation. The resulting single-IDA modified resin, after end-capping, acid washing, ultrapure water washing, ethylene glycol replacement, and pre-stabilization at 95℃, was used as the metal ion capture layer at the deionizer inlet. The single-IDA modified resin packing volume was 0.18 L, and the high-purity mixed-bed resin packing volume was 0.96 L.
[0091] Under the same test conditions as in Example 5, Fe in this comparative example 3+ Al 3+ Cu2+ Zn 2+ The times to reach C / CO=0.10 were 154 h, 162 h, 415 h, and 425 h, respectively; the times to reach C / CO=0.50 were 205 h, 215 h, 520 h, and 535 h, respectively; and the times to reach C / CO=0.95 were 273 h, 286 h, 661 h, and 682 h, respectively. These results indicate that the single-IDA modified resin, after self-grafting and low-precipitation treatment, exhibits superior metal ion capture ability compared to commercial IDA chelating resin systems, especially for Cu. 2+ and Zn 2+ It exhibits good penetration delay; however, due to the lack of phosphonic acid sites, it has limited effectiveness against Fe. 3+ And Al 3+ The ability to capture high-valence metal ions is still lower than that of the IDA-phosphonic acid dual-coordination modified resin system of this invention.
[0092] Comparative Example 4 The same IDA-phosphonic acid dual-coordination modified resin preparation process as in Example 5 was used. The difference was that after the resin was capped, acid-washed and ultrapure water-washed, it was not subjected to ethylene glycol-water replacement and 95°C high-temperature pre-stabilization treatment, but was directly filled into the deionizer inlet side.
[0093] When run in the same simulated coolant system as in Example 5, the initial outlet conductivity of this comparative example increased to 3.8 μS / cm, gradually decreasing and stabilizing below 2.0 μS / cm after 12 hours of operation; while the initial outlet conductivity of Example 5 was below 1 μS / cm. The TOC of the effluent in Comparative Example 4 was 28.6 mg / L in the first 24 hours, and the TOC of the effluent in Example 5 was 12.5 mg / L in the first 24 hours. These results indicate that ethylene glycol-water replacement and high-temperature pre-stabilization treatment can effectively reduce the risk of soluble ions and organic matter precipitation from the modified resin itself, making it more suitable for low-conductivity ethylene glycol coolant systems in fuel cells.
[0094] As shown in Example 5 and Comparative Examples 1-3, the IDA-phosphonic acid dual-coordination modified resin + mixed bed system of the present invention exhibits a longer dynamic breakthrough time for coolant contaminated with Fe, Al, Cu, and Zn composites. With C / CO = 0.10 as the initial breakthrough point, the Fe content in the system of the present invention... 3+ Al 3+ Cu 2+ Zn 2+The breakthrough times were 269 h, 282 h, 614 h, and 633 h, respectively, all significantly later than those of existing mixed-bed resin systems, commercial IDA chelating resin + mixed-bed systems, and single IDA modified resin + mixed-bed systems. These results indicate that this invention achieves selective capture of corrosive metal ions of different valence states at the front end through the synergistic coordination of IDA sites and phosphonic acid sites, effectively reducing the load on the downstream high-purity mixed-bed resin and thus extending the service life of the fuel cell ethylene glycol coolant deionizer.
[0095] The comparison of metal ion penetration curves of the ionizers prepared in Example 5 of this invention and Comparative Examples 1-3 in ethylene glycol coolant contaminated with Fe, Al, Cu, and Zn is shown in the figure below. Figure 5 .in, Figure 5 (a) is Fe 3+ Penetration curve, Figure 5 (b) is Al 3+ Penetration curve, Figure 5 (c) is Cu 2+ Penetration curve, Figure 5 (d) is Zn 2+ Breakthrough curves. In the figure, C / C0 represents the ratio of the outlet metal ion concentration to the initial inlet metal ion concentration. Running time is used to characterize the dynamic capture ability and breakthrough delay of different resin systems for metal ions. The curve results show that the existing mixed-bed resin (Comparative Example 1) mainly relies on ordinary ion exchange and lacks front-end selective capture ability for corrosive metal ions such as Fe, Al, Cu, and Zn continuously entering the coolant system, thus resulting in a short metal ion breakthrough time. When commercial IDA chelating resin is combined with the mixed-bed resin (Comparative Example 2), the breakthrough time for Cu... 2+ and Zn 2+ The penetration time of divalent transition metal ions is prolonged, but for Fe... 3+ Al 3+ The delaying effect of high-valence metal ions is limited; after combining the single IDA modified resin with the mixed bed resin (Comparative Example 3), due to the optimization of resin site cleanliness, group grafting density and low precipitation treatment, it exhibits a longer breakthrough time than the commercial IDA chelating resin system; after combining the IDA-phosphonic acid dual-coordination modified resin of this invention with the mixed bed resin, the IDA sites are utilized to target Cu 2+ Zn 2+ The multidentate chelation of divalent transition metal ions and the effect of phosphonic acid sites on Fe 3+ Al 3+The strong coordination of high-valence metal ions enables the synergistic capture of corrosive metal ions of different valence states, resulting in a significantly later metal ion penetration time compared to other comparative systems. This result indicates that the front-end low-precipitation dual-coordination modified resin described in this invention can effectively reduce the metal ion load of the back-end high-purity mixed-bed resin, allowing the back-end mixed-bed resin to primarily perform residual ion removal and low-conductivity polishing functions, thereby extending the low-conductivity maintenance life of the fuel cell glycol coolant deionizer.
[0096] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0097] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0098] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-precipitation dual-coordination modified resin for ethylene glycol coolant in fuel cells, characterized in that, The low-precipitation dual-coordination modified resin includes: Macroporous organic resin matrix; Iminodiacetic acid groups and phosphonic acid groups grafted onto the macroporous organic resin matrix.
2. The low-precipitation dual-coordination modified resin according to claim 1, characterized in that, The macroporous organic resin matrix includes at least one of macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy-based macroporous resin, amino-based macroporous resin, and weakly basic macroporous resin that can be modified secondary; and / or, The iminodiacetic acid group is used to capture Cu. 2+ Zn 2+ Ni 2+ Fe 2+ At least one of them; and / or, The phosphonic acid group is used to capture Fe. 3+ Al 3+ Cr 3+ At least one of them.
3. The low-precipitation dual-coordination modified resin according to claim 1, characterized in that, The content of the low-iminodiacetic acid groups is 0.2~2.5 mmol / g; the content of phosphonic acid groups is 0.05~1.5 mmol / g; and the total metal coordination capacity is 0.5~3.5 mmol / g; and / or, The low-precipitation dual-coordination modified resin has a particle size of 0.30~1.25 mm, a water content of 35~75%, a wet apparent density of 0.60~0.90 g / mL, a pore size of 10~100 nm, and a specific surface area of 20~800 m². 2 / g; and / or, After the low-precipitation dual-coordination modified resin is pre-stabilized in a 50% ethylene glycol-water mixture at 90-105℃ for 24-120 hours, the conductivity of its effluent is ≤20μS / cm and the TOC is ≤30mg / L.
4. A method for preparing the low-precipitation dual-coordination modified resin according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Pre-treat the macroporous organic resin matrix to obtain the pre-treated macroporous organic resin. S2. The pretreated macroporous organic resin matrix is swollen to obtain swollen resin. S3. React the swollen resin with iminodiacetic acid salt to introduce iminodiacetic acid groups and obtain the first modified resin; S4. Further amination of the remaining reactive sites of the first modified resin, and introduction of phosphonic acid groups through phosphonomethylation reaction to obtain a dual-coordination modified resin. S5. The dual-coordination modified resin is end-capped to seal residual chloromethyl sites, epoxy sites, or free reaction sites. S6. The end-capped dual-coordination modified resin is subjected to acid washing, ultrapure water washing, ethylene glycol-water replacement and pre-stabilization treatment in sequence to obtain the low-precipitation dual-coordination modified resin.
5. The preparation method according to claim 4, characterized in that, In step S1, the pretreatment includes: washing the macroporous organic resin matrix sequentially with ethanol, deionized water, 0.1~2.0 mol / L hydrochloric acid solution, deionized water, 0.1~2.0 mol / L sodium hydroxide solution, and deionized water until the conductivity of the washing solution stabilizes; and / or, In step S2, the swelling treatment is performed by impregnation with N,N-dimethylformamide, dimethyl sulfoxide, ethanol, water, methanol, or isopropanol; and / or, The swelling temperature is 20~80℃, and the swelling time is 2~24h.
6. The preparation method according to claim 4, characterized in that, In step S3, the iminodiacetic salt includes at least one of disodium iminodiacetic salt, trisodium iminodiacetic salt, and salts formed by in-situ neutralization of iminodiacetic acid with one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide; and / or, In step S3, the reaction temperature is 50–95°C, the reaction time is 4–36 h, and the pH of the reaction system is 8–12; and / or, The amination is performed using at least one of ammonia, ethylenediamine, diethylenetriamine, triethylenetetramine, ethanolamine, or diethanolamine; and / or, The phosphine methylation reaction uses at least one of phosphorous acid, phosphonic acid, hypophosphite, aminotrimethylenephosphonic acid, formaldehyde, or paraformaldehyde as a reactant, with a reaction temperature of 70–110 °C and a reaction time of 4–24 h; and / or, In step S5, the end-capping treatment is performed using ethanolamine, glycine, diethanolamine, triethanolamine, sodium carbonate, sodium sulfite, sodium thiosulfate, or a combination thereof, with an end-capping temperature of 30-90°C and an end-capping time of 2-24 hours; and / or, In step S6, the ethylene glycol-water replacement includes sequentially replacing the water with a 20-30% ethylene glycol-water mixture, a 40-60% ethylene glycol / water mixture, and a fuel cell-specific ethylene glycol coolant; the pre-stabilization treatment temperature is 90-105℃, and the treatment time is 24-120h.
7. A deionizer for ethylene glycol coolant in fuel cells, characterized in that, The deionizer includes a shell, a coolant inlet, a coolant outlet, and an inlet filter / flow distribution layer, a low-precipitation dual-coordination modified resin zone as described in any one of claims 1 to 5, a microporous partition, a high-purity mixed bed resin zone, and an outlet high-temperature fine filter layer, which are sequentially arranged inside the shell along the coolant flow direction.
8. The deionizer according to claim 7, characterized in that, The low-emission dual-coordination modified resin zone occupies 5-30% of the effective filling volume inside the deionizer; the high-purity mixed-bed resin zone occupies 60-90% of the effective filling volume inside the deionizer. The microporous partition includes a PPS microporous partition, a PTFE support mesh, a PPS support mesh, a PEEK microporous partition, a PVDF microporous partition, or a combination thereof; The pore size of the microporous partition is 50~500μm; The open area ratio is 30-70%; The inlet filtration / flow layer includes a high-temperature filter screen, high-temperature filter cotton, PPS fiber felt, PTFE support mesh, porous partitions, or a combination thereof; The outlet high-temperature fine filtration layer is a PPS sintered filter, PPS fiber felt, PTFE filter, PES filter, glass fiber filter, or a combination thereof.
9. The deionizer according to claim 8, characterized in that, The deionizer has an initial pressure drop of ≤15kPa at a coolant flow rate of 10LPM; the outlet coolant conductivity is ≤5μS / cm, and the initial outlet conductivity is ≤1μS / cm.
10. A liquid cooling system for a hydrogen fuel cell, characterized in that, The hydrogen fuel cell liquid cooling system includes hydrogen fuel cell heavy trucks, hydrogen fuel cell logistics vehicles, hydrogen fuel cell buses, stationary fuel cell systems, fuel cell backup power systems, or other electrochemical systems that use ethylene glycol / water low-conductivity coolant.